2002
DOI: 10.1080/0144361021000020333
|View full text |Cite
|
Sign up to set email alerts
|

The relative risk of 'fetal distress' in pregnancy associated with meconium-stained liquor at different gestation

Abstract: Pregnancies complicated with meconium-stained liquor are regarded as at risk of fetal distress. Evidence from animal and human studies indicate that passage of meconium may be related to fetal maturity. This retrospective study attempts to quantify the relative risk of non-reassuring cardiotocography or 'fetal distress' in pregnant women complicated by meconium-stained liquor for preterm, term and post-term pregnancies. A total of 9542 singleton pregnancies, delivered in a tertiary obstetric unit in Hong Kong … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 32 publications
4
20
2
Order By: Relevance
“…The reason for higher incidence of LSCS in our study among the cases was because of associated abnormal CTG findings especially in patients with thick meconium. Similar results were noted by Gupta et al, Naqvi et al, Khatun et al, Wong SF et al, Mundhra et al 7,9,10,12,13 Apgar score was noted in all the babies at 1 minute and 5 minutes and resuscitation was done in non-vigorous babies with low APGAR score. One baby in each group had APGAR score of 0 at birth and after resuscitation in our study.…”
Section: -11supporting
confidence: 76%
“…The reason for higher incidence of LSCS in our study among the cases was because of associated abnormal CTG findings especially in patients with thick meconium. Similar results were noted by Gupta et al, Naqvi et al, Khatun et al, Wong SF et al, Mundhra et al 7,9,10,12,13 Apgar score was noted in all the babies at 1 minute and 5 minutes and resuscitation was done in non-vigorous babies with low APGAR score. One baby in each group had APGAR score of 0 at birth and after resuscitation in our study.…”
Section: -11supporting
confidence: 76%
“…The incidence of thick meconium was significantly higher in patients with post term pregnancy (15.71% vs 2.5% p=0.004), oligohydramnios (12.8% vs 1.2 %, p=0.01) and in unbooked cases (44.2% vs 18.7%, p=0.007. Similar findings were seen in the studies done by Wong et al, Sheiner et al and Yinka Oyelese et al [10][11][12] The increased incidence of meconium staining in oligohydramnios may be the result of intrapartum fetal distress as a consequence of cord compression. It is also likely that meconium released into an already reduced amniotic fluid volume causes thick, viscous meconium staining.…”
Section: Discussionsupporting
confidence: 88%
“…respiratory distress syndrome (RDS), hypoglycemia, and seizures. 1,3,4,[12][13][14][15][16] Nevertheless, most studies that demonstrated increased rate of perinatal complications in women with MSAF addressed a heterogeneous obstetrical population of low-and high-risk pregnancies. While some did not exclude maternal comorbidities, others reported pregnancy outcome in high-risk pregnancies, and moreover included preterm deliveries, 2,3 which are all considered independent risk factors for adverse perinatal outcomes.…”
mentioning
confidence: 99%